Sensibilities and human and non-human readjustments in the narrative of Cristina Rivera Garza (Anclajes, 2020)
I suggest a reflection upon two books that explore a reconstitution and an enlargement of the human and non-human living. Cristina Rivera Garza’s El mal de la taiga (2012) and Había mucha neblina o humo o no sé qué (2016) offer imaginative openings that depose the individual subject as a paradigm, and the community as a social group linked to a territory. Those narratives track possible relations between the human and the living, territory and culture, geographic materials and collectivities; but they also display formal creative elements as well as reading and writing processes that are committed with this imaginative opening. The agreement between literature experience and vital confluence calls a regime of sensibilities that combines not only the past and present times but also an experience of virtual times together with a sensitive and cognitive contemporary condition. The enhancement of formal, material and scriptural registers in the production of Rivera Garza inspires an essential hypothesis; that is to say, modulating and renewing the writing is the sine qua non condition to explore new modes of conception of the un(human) subject and the community.
Keywords: Cristina Rivera Garza; Posthumanism; Recent Narrative; Imagination; Community